Planning for the informal sector enterprises in the Central Region: implications for growth centres and regional planning in Ghana - Yankson, Paul William Kojo (1979)
The purpose of this study was to: Examine the potential for employment growth and output in the informal sector in the Central Region of Ghana; and to: outline a strategy for the development of the enterprises in the sector in the region; and to discuss the implications of the strategy for the Regional Planning Organization and the implementation of a growth centre strategy in the region.